Optimisation of dispersive liquid-liquid microextraction for plasma sample preparation in bioanalysis of CDK4/6 inhibitors in therapeutic combinations for breast cancer treatment - Lu Turković; Natan Koraj; Zvonimir Mlinarić; Tajana Silovski; Slaven Crnković; Miranda Sertić (Heliyon, 2023)
Cyclin D dependent kinase 4 and 6 (CDK 4/6) inhibitors are novel anticancer drugs used in therapeutic combinations with endocrine therapy for breast cancer treatment. Their determination in patient plasma is of high interest as a prerequisite for possible therapeutic drug monitoring. Dispersive liquid-liquid microextraction (DLLME) shows great potential in bioanalytical sample preparation. Its simplicity and speed, along with the suitability for using small amounts of sample and hazardous solvents are some of its main advantages. However, its application on plasma samples is scarce and requires further development. The aim of this work was to explore the applicability of DLLME in the simultaneous extraction of six drugs of interest from human plasma, with an emphasis placed on achieving high extraction recoveries with low sample and solvent consumption. To tackle the low availability and amount of the plasma sample, as well as the complexity of the biological matrix, three novel DLLME modes are proposed: organic sample DLLME (OrS-DLLME), aqueous sample DLLME (AqS-DLLME), and a modified air-assisted DLLME (AA-DLLME). The extractant and disperser type and volume, volume ratios of all the components in the ternary system, effect of pH and salting out were optimised for all three proposed modes of DLLME. Optimised representative DLLME-HPLC-DAD-FLD method was validated and shown to be linear (R > 0.994), precise (RSD ≤13.8%, interday), accurate (bias −13.1–13.1%, interday) and robust (relative effect −3.34–6.08%). Simultaneous extraction of all six drugs with high recoveries (81.65–95.58%) was achieved. Sample volumes used were as low as 50–100 μL, with necessary organic solvent volumes in μL ranges. Greenness scores obtained using the AGREE software were between 0.63 and 0.66, demonstrating compliance with green analytical chemistry principles. Finally, the validated method was successfully applied on breast cancer patient plasma samples.